Targeting Bacterial Sortases in Search of Anti-virulence Therapies with Low Risk of Resistance Development - Georgiana Nitulescu; Denisa Margina; Anca Zanfirescu; Octavian Tudorel Olaru; George Mihai Nitulescu (Pharmaceuticals, 2021)
Increasingly ineffective antibiotics and rapid spread of multi- and pan-resistant bacteria represent a global health threat; hence, the need of developing new antimicrobial medicines. A first step in this direction is identifying new molecular targets, such as virulence factors. Sortase A represents a virulence factor essential for the pathogenesis of Gram-positive pathogens, some of which have a high risk for human health. We present here an exhaustive collection of sortases inhibitors grouped by relevant chemical features: vinyl sulfones, 3-aryl acrylic acids and derivatives, flavonoids, naphtoquinones, anthraquinones, indoles, pyrrolomycins, isoquinoline derivatives, aryl β-aminoethyl ketones, pyrazolethiones, pyridazinones, benzisothiazolinones, 2-phenyl-benzoxazole and 2-phenyl-benzofuran derivatives, thiadiazoles, triazolothiadiazoles, 2-(2-phenylhydrazinylidene)alkanoic acids, and 1,2,4-thiadiazolidine-3,5-dione. This review focuses on highlighting their structure–activity relationships, using the half maximal inhibitory concentration (IC50), when available, as an indicator of each compound effect on a specific sortase. The information herein is useful for acquiring knowledge on diverse natural and synthetic sortases inhibitors scaffolds and for understanding the way their structural variations impact IC50. It will hopefully be the inspiration for designing novel effective and safe sortase inhibitors in order to create new anti-infective compounds and to help overcoming the current worldwide antibiotic shortage.